Prevalence of Home Births and Associated Risk Profile and Maternal Characteristics, 2016–2018. Issue 6 (December 2020) - Goyal, Sonal; Kortsmit, Katherine; Cox, Shanna; D'Angelo, Denise V.; Romero, Lisa; Henderson, Zsakeba T.; Barfield, Wanda D.
Abstract : OBJECTIVE: To estimate the prevalence of pregnancies that meet the low-risk criteria for planned home births and describe geographic and maternal characteristics of home births compared with hospital births. METHODS: Data from the 2016–2018 Pregnancy Risk Assessment Monitoring System (PRAMS), a survey among women with recent live births, and linked birth certificate variables were used to calculate the prevalence of home births that were considered low-risk. We defined low-risk pregnancy as a term (between 37 and 42 weeks of gestation), singleton gestation with a birth weight within the 10th–90th percentile mean for gestational age (as a proxy for estimated fetal size appropriate for gestational age), without prepregnancy or gestational diabetes or hypertension, and no vaginal birth after cesarean (VBAC). We also calculated the prevalence of home and hospital births by site and maternal characteristics. Weighted prevalence estimates are presented with 95% CIs to identify differences. RESULTS: The prevalence of home births was 1.1% (unweighted n=1, 034), ranging from 0.1% (Alabama) to 2.6% (Montana); 64.9% of the pregnancies were low-risk. Among the 35.1% high-risk home births, 39.5% of neonates were large for gestational age, 20.5% of neonates were small for gestational age, 17.1% of the women had diabetes, 16.9% of the women had hypertension, 10.6% of the deliveries were VBACs, and 10.1% of the deliveries were preterm. A significantly higher percentage of women with home births than hospital births were non-Hispanic White (83.9% vs 56.5%), aged 35 years or older (24.0% vs 18.1%), with less than a high school-level of education (24.6% vs 12.2%), and reported no health insurance (27.0% vs 1.9%). A significantly lower percentage of women with home births than hospital births initiated prenatal visits in the first trimester (66.9% vs 87.1%), attended a postpartum visit (80.1% vs 90.0%), and most often laid their infants on their backs for sleep (59.3% vs 79.5%). CONCLUSIONS: Understanding the risk profile, geographic distribution, and characteristics of women with home births can guide efforts around safe birthing practices. Abstract : The geographical prevalence, risk profile, and maternal characteristics of home births can be used to guide efforts around safe birthing practices.